PENGARUH INTERAKSI KONSENTRASI DAN WAKTU APLIKASI PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI SAWAH (Oryza sativa L) VARIETAS SERAYU - Dellyna Rombon; Jemmy Najoan; Semuel D. Runtunuwu (COCOS, 2018)
ABSTRACT This study aims to determine the effect of the interaction between the concentration and time of application of paclobutrazol to the growth and yield of wetland rice, The experiment was carried out for 4 months in Sulu Village , Tatapaan Indah District, South Minahasa Regency, starting from May to August 2014. The experiment was carried out using the Randomized Block Design (RBD) method, with two treatment factors namely paclobutrazol concentration, consisting of three concentrations namely: 1). P1 (0 ppm), 2). P2 (400 ppm), 3). P3 (600 ppm), and Time of paclobutrazol application (W), namely: 1). W1 is sprayed at plant age 30 HST, 2). W2 is sprayed at plant age 37 HST, 3). W3 is sprayed at plant age 44 HST. Observations were made on: Plant height, number of productive tillers, harvested dry grain, paddy filled with paddy, weight of paddy filled with clumps. Data were analyzed by variance and the smallest real difference test was BNT 0.5%. The time and concentration of administration of paclobutrazol only interact significantly in plant height. The concentration of paclobutrazol (singly) has a significant effect on: 1). Dry paddy harvest, 2). Number of grains containing clumps, 3). grain weight containing clumps. Keywords: paddy, paclobutrazol, concentration, date of application, interaction.